2019
DOI: 10.1029/2018gl080930
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Data Assimilation Without a Dense Observation Network

Abstract: The tsunami data assimilation method enables tsunami forecasting directly from observations, without the need of estimating tsunami sources. However, it requires a dense observation network to produce desirable results. Here we propose a modified method of tsunami data assimilation for regions with a sparse observation network. The method utilizes interpolated waveforms at virtual stations. The tsunami waveforms at the virtual stations between two existing observation stations are estimated by shifting arrival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…However, this result may not indicate that the scenario 4 (involving two OBPGs) will give the same forecast accuracy for other tsunamis with different sizes and strike angles. Our experience (Wang et al 2019) showed that the larger the tsunami size and wavelength, the more OBPGs is required for accurate TDA. Clearly, detailed sensitivity analyses considering various earthquake scenarios (magnitude, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…However, this result may not indicate that the scenario 4 (involving two OBPGs) will give the same forecast accuracy for other tsunamis with different sizes and strike angles. Our experience (Wang et al 2019) showed that the larger the tsunami size and wavelength, the more OBPGs is required for accurate TDA. Clearly, detailed sensitivity analyses considering various earthquake scenarios (magnitude, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The tsunami DA method proposed by Maeda et al (2015) for simulating tsunami wavefields in real-time is based on the optimal interpolation method, which has a lower computational cost than the more advanced method using the ensemble Kalman filter, under the assumption that the system is linear. Even though the optimal interpolation method is simple, however, the DA approach showed good agreement with real tsunami data (Gusman et al 2016;Heidarzadeh et al 2019;Wang et al 2017Wang et al , 2019a and the synthetic case (Mulia et al 2017). In the numerical simulation, the tsunami wavefield at the nth time step is represented as x n η n�t, x, y , M n�t, x, y , N n�t, x, y , where η is the tsunami height, M and N are the depthintegrated tsunami fluxes in the x and y directions and t is the time step.…”
Section: Data Assimilationmentioning
confidence: 95%
“…ε f and ε O are the errors of the forward simulation and observations, respectively, while ε f T and ε OT are the corresponding transpose matrices. We assume the Gaussian-distributed errors to compute both covariance matrices, with a characteristics distance of 20 km (Maeda et al 2015;Wang et al 2019a).…”
Section: Data Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here ε f represents the errors in numerical forecast between two grids, and ε O represents the observational errors of observation stations. We used the Gaussian‐distributed errors to compute the error covariance matrices, with a characteristic distance of 20 km (Maeda et al, ; Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%